1992
DOI: 10.1128/aac.36.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a polymerase chain reaction assay and a conventional microbiologic method for detection of methicillin-resistant Staphylococcus aureus

Abstract: The presence or absence of a methicillin resistance gene in 58 clinical isolates of Staphylococcus aureus was examined by the polymerase chain reaction (PCR) and Southern blot analyses. The results were analyzed in relation to those of the MIC assay of methicillin and oxacillin. PCR assay results were identical to those of Southern blot analysis of genomic DNA digested with HindIII (positive, 28 strains; negative, 30 strains). Among the 28 PCR-positive strains, 6 strains showed methicillin susceptibility by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
1
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 18 publications
(8 reference statements)
0
70
1
4
Order By: Relevance
“…A total of 359 MRSA isolates were collected between 1961 and 1999 from 20 countries. Isolates were confirmed as MRSAs in our laboratory by detecting the presence of the mecA gene with PCR (14). The collection contains members of previously described EMRSA clones, including the Iberian (15), Portuguese͞Brazilian (16), Vienna (17), New York͞Japanlocus to those of the known alleles in the S. aureus MLST database.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 359 MRSA isolates were collected between 1961 and 1999 from 20 countries. Isolates were confirmed as MRSAs in our laboratory by detecting the presence of the mecA gene with PCR (14). The collection contains members of previously described EMRSA clones, including the Iberian (15), Portuguese͞Brazilian (16), Vienna (17), New York͞Japanlocus to those of the known alleles in the S. aureus MLST database.…”
Section: Methodsmentioning
confidence: 99%
“…Among 126 S. aureus, 54 isolates were positive for the mecA gene by PCR, remaining 74 S. aureus were negative (Table I). Schmitz et al, (1997) and Tokue et al, (1992) previously reported that the utility of PCR for the accurate detection of the mecA gene and the possibility of simultaneous identification of S. aureus and detection of mecA gene. During the last decade, many studies have demonstrated the extremely high capacity of PCR for specifically detecting bacteria and genes of interest (Salisbury et al, 1996).…”
Section: Detection Of Meca Gene By Pcrmentioning
confidence: 99%
“…The rationale for using ceftizoxime and aztreonam in the selective broth instead of oxacillin and colistin was that earlier studies had shown that both oxacillin and colistin resulted in inhibited or slower growth of MRSA strains (data not shown). Furthermore, ceftizoxime is known to increase the phenotypic level of resistance to methicillin (8,12,13).…”
mentioning
confidence: 99%